Comparação energética de diferentes métodos de secagem de alimentos utilizando código computacional EES - Ubaldine, Danilo Torquato (2022)
The food drying process has several benefits, such as ease of storage, reduction of microbial contamination and ease of transport. However, it is a process that usually consumes a lot of energy. The present work presents a study that approaches the drying of foods, from a thermodynamic evaluation of the objects of study. The structure of the work consists of five chapters, and its main goal is to carry out a comparative analysis between two different scenarios of food drying, the first scenario consisting of a heat pump food dryer, and the second scenario consisting of a electrical resistance dryer. The first step was developing a systematic review to evaluate the various studies developed in the area of interest. The second step was developing a thermodynamic evaluation of the heat pump dryer, through an application of the first and second laws of thermodynamics. A parametric analysis and a comparison with different refrigerants were also developed. The next step was developing a thermodynamic evaluation of the electric resistance dryer and a comparison with the heat pump dryer. The thermodynamic estimates were made with the aid of the Engineering Equation Solver computer program. From the study, it was possible to verify that the heat pump dryer presented significantly better results than the electric resistance dryer in relation to energy consumption and entropy generation. Drying using an electric resistance dryer showed an increase of 29.9% in energy demand for drying sweet potato and 74.7% for drying cassava. Regarding entropy, the electric resistance dryer showed higher values than the heat pump dryer dryer using R717 coolant fluid in all analyzed studies. Finally, an analysis of the aid of photovoltaic energy for the energy of the demand energy dryers was developed, to find the necessary area to generate the drying process. The work showed that the use of heat pump dryers in the drying process is a viable alternative in a thermodynamic point of view, for a reduction of energy consumption and waste.